Study on the Mechanism and Dose–Effect Relationship of Flavonoids in Different Extracts of Radix Hedysari Against Gastrointestinal Injury Induced by Chemotherapy - Shasha Zhao; Miaomiao Yang; Zimu Yang; Hai He; Ziyang Wang; Xinyu Zhu; Zhijia Cui; Jing Shao (Pharmaceuticals, 2025)
Background: Previous studies have shown Radix Hedysari (RH)’s gastroprotective potential, but its active components and mechanisms remain uncharacterized. This study aimed to identify RH’s bioactive fractions, elucidate protection mechanisms, establish flavonoid dose-effect relationships, and determine the pharmacodynamic basis. Methods: Chemical profiling quantified eight flavonoids via HPLC. Network pharmacology screened targets/pathways using TCMSP, GeneCards databases. In vivo validation employed cisplatin–induced injury models in Wistar rats (n = 10/group). Assessments included: behavioral monitoring; organ indices; ELISA (MTL, VIP, IFN–γ, IgG, IL–6, TNF–α etc.); H&E; and Western blot:(SCF, c–Kit, p65). Dose–effect correlations were analyzed by PLS–DA. Results: Content determination indicated that Calycosin–7–glucoside and Ononin were notably enriched on both the n–BuOH part and the EtOAc part. Network pharmacology identified 5 core flavonoids and 8 targets enriched in IL–17/TNF signaling pathways. n–BuOH treatment minimized weight loss vs. MCG, increased spleen/thymus indices. n–BuOH and HPS normalized gastrointestinal, immune, inflammatory biomarkers (p < 0.01 vs. MCG). Histopathology confirmed superior mucosal protection in n–BuOH group vs. MCG. Western blot revealed n–BuOH significantly downregulated SCF, c–kit, and p65 expressions in both gastric and intestinal tissues (p < 0.001 vs. MCG). PLS–DA demonstrated Calycosin–7–glucoside had the strongest dose–effect correlation (VIP > 1) with protective outcomes. Conclusions: The n–BuOH fraction of RH is the primary bioactive component against chemotherapy–induced gastrointestinal injury, with Calycosin–7–glucoside as its key effector. Protection is mediated through SCF/c–Kit/NF–κB pathway inhibition, demonstrating significant dose–dependent efficacy. These findings support RH’s potential as a complementary therapy during chemotherapy.